Right ventricular function in transcatheter mitral and tricuspid valve edge-to-edge repair - Stolz, Lukas; Doldi, Philipp M.; Weckbach, Ludwig T.; Stocker, Thomas J.; Braun, Daniel; Orban, Martin; Wild, Mirjam G.; Hagl, Christian; Massberg, Steffen; Näbauer, Michael; Hausleiter, Jörg; Orban, Mathias (Frontiers in Cardiovascular Medicine, 2022)
Since transcatheter edge-to-edge repair (TEER) has become a valuable therapy in the treatment of both, mitral (MR) and tricuspid regurgitation (TR), the question of optimized patient selection has gained growing importance. After years of attributing rather little attention to the right ventricle (RV) and its function in the setting of valvular heart failure, this neglect has recently changed. The present review sought to summarize anatomy and function of the RV in a clinical context and aimed at presenting the current knowledge on how the RV influences outcomes after TEER for atrioventricular regurgitation. The anatomy of the RV is determined by its unique shape, which necessitates to use three-dimensional imaging methods for detailed and comprehensive characterization. Complex parameters such as RV to pulmonary artery coupling (RVPAc) have been developed to combine information of RV function and afterload which is primary determined by the pulmonary vasculature and LV filling pressure. Beyond that, TR, which is closely related to RV function also plays an important role in the setting of TEER. While M-TEER leads to reduction of concomitant TR in some patients, the prognostic value of TR in the setting of M-TEER remains unclear. Overall, this review summarizes the current state of knowledge of the outstanding role of RV function and associated TR in the setting of TEER and outlines the unsolved questions associated with right-sided heart failure.